Metronomic oral doxorubicin in combination of Chk1 inhibitor MK-8776 for p53-deficient breast cancer treatment. (November 2018) - Chung, Seung Woo; Kim, Gui Chul; Kweon, Seho; Lee, Hanul; Choi, Jeong Uk; Mahmud, Foyez; Chang, Hyo Won; Kim, Ji Won; Son, Woo-Chan; Kim, Sang Yoon; Byun, Youngro
Abstract: Metronomic chemotherapy, which is defined as a low-dose and frequent administration of cytotoxic drugs without drug-free breaks, has been recently emerged as an alternative to traditional MTD therapy and has shown therapeutic benefit in breast cancer patients in numbers of clinical studies. Unlike MTD, metronomic chemotherapy acts by multiple mechanisms including antiangiogenic effect and immunomodulation, but the direct cytotoxic effect only playing a minor role due to the lowered dose. In this light, within the limits of p53-deficient breast cancer, we demonstrate the enhanced anticancer effect of metronomic chemotherapy using doxorubicin when combined with Chk1 inhibitor MK-8776 by specifically augmenting the direct cytotoxic effect on cancer cells. Since the oral drug is greatly favored in metronomic chemotherapy due to the frequent and potential long-term administration, we prepared an oral doxorubicin by producing an ionic complex with deoxycholic acid, which showed sufficient bioavailability and anticancer effect when administered orally. MK-8776 selectively enhanced the cytotoxic effect of low-concentration doxorubicin in p53-deficient breast cancer cells by abrogating the Chk1-dependent cell cycle arrest in vitro . Consistently, combining MK-8776 significantly improved the anticancer effect of the daily administered oral doxorubicin in p53-deficient breast cancer xenografts especially in a lower dose of doxorubicin without evident systemic toxicities. Combination therapy of MK-8776 and metronomic oral doxorubicin would be thus promising in the treatment of p53-deficient breast cancer benefited from the augmented direct cytotoxic effect and low risk of toxicities.